Theoretical characterisation of the radial and translational motion of coated microbubbles under acoustic excitation - Harfield, C; Ovenden, N; Memoli, G; Jones, P; Stride, E (2013)
Ultrasound contrast agents, in the form of coated microbubbles, are a powerful tool in current diagnostic imaging. Given their sensitive dynamic response they also have the potential to be used for quantitative measurements of the properties of the surrounding tissue (e.g. percentage perfusion or blood pressure). For this potential to be realised, however, the theoretical descriptions of bubble behaviour, in particular the constitutive equations for the microbubble shell, need to be improved and a method needs to be developed for the accurate characterisation of individual bubbles. In this paper the first steps are taken towards deriving a complete model for the coupled radial and translational motion of a coated bubble. It is then shown that with this model the bubble can be characterised by a unique set of parameters describing the bubble shell corresponding to its viscous and elastic response. This uniqueness will enable the model to be used to interpret experimental data and quantify these parameters for which accurate values are currently lacking but which are critical to predicting bubble response and hence enabling advanced diagnostic applications. © Published under licence by IOP Publishing Ltd.